Domingos Álvares, African healing, and the intellectual history of the Atlantic world - Sweet, James H. (James Hoke) (University of North Carolina Press, 2011)
By tracing the steps of Domingos Alvares, a powerful African healer and vodun priest, James Sweet finds dramatic means for unfolding a history of the eighteenth-century Atlantic world in which healing, religion, kinship, and political subversion were intimately connected.